PENGARUH KEPEMIMPINAN, LINGKUNGAN KERJA, DAN KOMPENSASI TERHADAP KINERJA PEGAWAI PADA KANTOR BIRO PERENCANAAN DAN ORGANISASI, KEMENTERIAN LUAR NEGERI - Mikin Sentono; Sitorus, Guston; Robi Wijaya (Jurnal Satya Mandiri Manajemen dan Bisnis, 2023)
This study aims to determine the effect of leadership, work environment, and compensation on employee performance at the Office of the Bureau of Planning and Organization of the Ministry of Foreign Affairs. The research design used is quantitative causal research to determine the effect of the independent variables on the dependent variable. Data collection techniques through observation, questionnaires/questionnaires with a total of 66 respondents from a population of 66 people by conducting validity and reliability tests with multiple linear regression data analysis: F test, t test, and R2 test. The data was processed using the Multivariete Analysis Application with the IBM SPSS 25 Program. The results based on analysis and hypothesis testing show that there is a significant influence between leadership, work environment, and compensation on employee performance at the Bureau of Planning and Organization of the Ministry of Foreign Affairs. According to the multiple linear regression analysis test, compensation has a very large influence on employee performance.